Solving Numerical Problems in Chemistry and Physics: Ideas for High School Teachers - Kumar, David Devraj; Persin, Ronald (Voices of Teachers and Teacher Educators, 2019)
This paper presents literature-based ideas for teaching numerical problem solving in high school science, specifically in Chemistry and Physics. Factors contributing towards success in problem solving are discussed. The importance of prior subject-matter knowledge, and a single strategy applicable to different types of problems are emphasised. Selected examples of problems with solution strategies from high school Chemistry and Physics are outlined. Implications for problem solving in science teacher preparation are explained. Recommendations for science teachers to utilise in their teaching are provided.